Energy evolution law and catastrophic failure prediction of Luohe formation sandstone during rupture process experienced one freeze-thaw cycle - Liang Zhang; Jianxi Ren; Mengchen Yun; Yichen Zhang; Bolong Liu; Kun Zhang (PLoS ONE, 2025)
To explore the energy damage evolution law and catastrophic failure characteristics of sandstone in Luohe Formation after thawing, the uniaxial compression tests on sandstone after one freeze-thaw cycle with different freezing temperatures were conducted. The mechanical properties and failure mode of thawed sandstone were analyzed. Furthermore, the energy evolution and its sensitivity to freezing temperature during deformation and failure were investigated. Subsequently, a model was proposed to predict the catastrophic failure time of the thawed sandstone in the Luohe Formation. The results showed that the peak strength and elastic modulus of thawed sandstone decrease with the decrease of freezing temperature. The failure modes of the thawed sandstone can be classified into axial splitting failure, shear failure, and tensile-shear mixed failure. Additionally, with the decrease of freezing temperature, the strain energy release rate and dissipation energy growth rate of rock samples decrease. Energy damage process of the Luohe Formation sandstone after thawing is divided into stages of minor damage, deceleration damage, damage steadily increase, damage accelerated increase, and damage sharply increase. The thawed sandstone catastrophic failure presents a clear critical power-law singularity behavior, and its critical singularity characteristic value β is roughly 0.7±0.1. The proposed catastrophic failure prediction method yields a prediction time of imminent rock failure (tf p=4.356 min) that is very close to the actual failure time (tf=4.376 min) at freezing temperature of -10 °C, and the prediction results are good and stable.